PREDICTING ROLE OF EMOTIVE AND BEHAVIOR PROBLEMS ON COGNITIVE FUNCTIONING AMONG WOMEN BURN VICTIMS (Journal of Medical & Health Sciences Review, 2025)
Burn damages directly lead to hinder the physical body but there is also substantial impact occur on the psychological and cognitive functioning. The present study expected to examine the predictive power of emotive (depression, anxiety), and behavior issues (conduct problems) on the cognitive functioning among women burn victims. A cross sectional research design was used. The data were collected from women burn victims by using standardized measures Psychological Adjustment Scale for Adults that assess the depression, anxiety, conduct problems whereas the MoCA scale was used to measure the cognitive performance. The findings revealed that overall depression, anxiety and conduct problems predict the cognitive functioning F(3, 196) = 21.50, p < .001. Further, 24.8% of the explained variance in cognitive functioning was due to anxiety, depression, and conduct problems (R2 = .248). Whereas if explore the variables individually, only anxiety was the predictor of cognitive functioning. It entails that anxiety significantly associated with poorer cognitive functioning among the variables studied. These results highlight the prominence of addressing psychological well-being in recovery programs to intact cognitive functioning and improve the lives of women burn survivors.